MEDICAL AND SOCIAL ASPECTS OF THE PROBLEM OF SURGICAL TREATMENT OF MORBID OBESITY (Literature review) - Botirov , Akram; Rasulov , Murodzhon (Medical science of Uzbekistan, 2023)
In this literature review, the authors note that worldwide there has been a clear trend towards a steady increase in obesity, including morbid obesity. A number of studies are devoted to this problem, where questions of etiopathogenesis, methods of conservative and surgical treatment are studied. However, despite the successes achieved, in 90-95% of cases, conservative therapy is unsuccessful, and in surgical treatment in 60% of cases there are complications in the long term, which require repeated surgical treatment in 25% of cases. This circumstance, in our opinion, is due to the lack of specific treatment and diagnostic algorithms, as well as insufficient attention to comorbidities requiring simultaneous surgery, which causes an urgent need for further research.